Regulation of Prothrombinase Activity by Protein S - van't Veer, Cornelis; Butenas, Saulius; Golden, Neal J.; Mann, Kenneth G. (Thrombosis and Haemostasis, 1999)
The independent effect of protein S as prothrombinase inhibitor has been proposed to depend on binding to both coagulation factors Va and factor Xa or on the binding to phospholipid thereby limiting the phospholipid available for prothrombinase activity. In this study we show that plasma concentrations of protein S (300 nM) equilibrated with the prothrombinase components (factor Va, factor Xa, phospholipid) cause a profound inhibition at low phospholipid concentrations (~0.2 μM). This inhibition by protein S of prothrombinase activity is abrogated with increasing phospholipid concentrations. Modeling of the effect of protein S on prothrombinase based only on the reported affinity of protein S for phospholipids (Kd ~ 10-8 M) in an equilibrium model (Clotspeed), predicted the experimentally obtained thrombin generation rates at low phospholipid in the presence of protein S based on the diminished available phospholipid binding sites for the prothrombinase components. Consistently, initial rates of prothrombinase activity are already maximally inhibited when protein S is preincubated with the phospholipid prior to the addition of factor Xa, factor Va and pro-thrombin. The results indicate that the order of addition of prothrombinase components and the availability of phospholipid may have a profound influence on observed effects of protein S on prothrombinase activity. All prothrombinase components (factor Xa, factor Va, phospholipid) become available during the course of the physiological thrombin generation. The effect of protein S was therefore studied on tissue factor-induced, platelet-dependent thrombin generation. Protein S delayed and inhibited the rate of thrombin generation of tissue factor-induced thrombin formation when surface is provided at physiologic concentrations using isolated platelets (2 × 108/ml). In contrast, protein S hardly affected thrombin generation in this model when platelets were pre-activated with collagen. Furthermore, the observed effects of addition of protein C and thrombomodulin in the absence or presence of protein S on tissue factor-induced, platelet-dependent thrombin generation, indicate that protein S and protein C may cooperate in the regulation of prothrombinase activity through independent mechanisms.